Pengaruh Pertumbuhan Ekonomi dan Upah Minimum Terhadap Jumlah Pengangguran di Provinsi Nusa Tenggara Timur - Wandal, Mertisari Konga; Renggo, Yuniarti Reni; Hudang, Adrianus Kabubu (Jurnal Ilmiah Global Education, 2024)
A country that is actively trying to improve the welfare of its population is Indonesia, which is still considered a backward country. The government has implemented various steps to achieve social welfare, although there are still several obstacles that have not been fully overcome, such as the issue of unemployment. Resolving this problem is a collective task that must be addressed effectively and continuously. This research aims to determine the influence of economic growth and regional minimum wages on the number of unemployed in East Nusa Tenggara Province. The research method uses quantitative methods with secondary data from publications from the Central Statistics Agency of East Nusa Tenggara Province. The data used is panel data, covering the 2018-2022 time series and cross-sections from 22 districts/cities. Based on the research results, economic growth has a positive and significant effect on the number of unemployed. and also, the regional minimum wage has a positive but insignificant effect on the number of unemployed.